ΤΑ ΜΑΘΗΤΙΚΑ ΧΡΟΝΙΑ ΤΟΥ ΚΩΝΣΤΑΝΤΙΝΟΥ ΒΟΛΑΝΑΚΗ ΣΤΗ ΣΥΡΟ ΚΑΙ Ο ΔΑΣΚΑΛΟΣ ΙΧΝΟΓΡΑΦΙΑΣ ΑΝΔΡΕΑΣ ΚΡΙΕΖΗΣ - ΑΛΕΒΙΖΟΥ, ΝΤΕΝΙΖ ΧΛΟΗ (Μνήμων, 2005)
Denise-Ghloe Alevizou, The school-years of Konstantinos Volanakis in Syros and his art teacher Andreas Kriezis Research in the state archives at Hermoupolis, Syros and specifically in the Hermoupolis school registers of the mid 19th century, allows us today to establish that Konstantinos Volanakis attended classes there from 1851/1852 through to 1854/1855. The presumption that he actually completed his education there remains however unfounded. Yet, whilst his graduation from the Hermoupolis Gymnasion (High school) remains doubtful, our search in the teachers' records of the same period establishes that the then already renowned artist Andreas Kriezis may now be safely connected to the young schoolboy, as his art teacher there. This hitherto unsuspected connection between the two important 19th century artists, strengthened or not by an oil painting of the «Parthenon» on the walls of the Gymnasion (attributed by hearsay to Volanakis, but probably a work by Kriezis), sheds new light on the early period of the great sea-scapist allowing us at the same time to assume a possible constructive role by Kriezis.